Image quality evaluation of ultrasound imaging systems: advanced B‐modes. Issue 3 (12th March 2019) - Sassaroli, Elisabetta; Crake, Calum; Scorza, Andrea; Kim, Don‐Soo; Park, Mi‐Ae
Abstract: The Quality assurance of ultrasound clinical imaging systems is essential for maintaining their performance to the highest level and for complying with the requirements by various regulatory and accrediting agencies. Although there is no standardization yet, most of the quality assessment procedures available in literature are proposed for B‐mode and Doppler imaging. However, ultrasound imaging systems offer a variety of advanced imaging modes, besides B‐mode and Doppler, which are primarily aimed at improving image quality. This study presents computer‐based methods for evaluating image quality for the advanced imaging modes of ultrasound imaging systems: harmonic imaging, spatial compounding imaging, adaptive speckle reduction, and tissue aberration correction. The functions and parameters proposed for evaluating image quality are: grayscale mapping function, image contrast, contrast‐to‐noise ratio (CNR), and high‐contrast spatial resolution. We present our computer‐based methods for evaluating image quality of these modes with a number of probe and scanner combinations, which were employed to image targets in ultrasound phantoms. The functions and parameters here proposed in image quality performance evaluation are: grayscale mapping function, image contrast, CNR, and high‐contrast spatial resolution. We show that these quantities could be useful in developing standardized methods for evaluating the advanced ultrasound imaging modes, especially when the advanced mode resulted in subtle visual differences.